UJI HOMOGENITAS DAN HETEROGENITAS CLUSTER DATA INTERKOMPARASI ANAK TIMBANGAN - Arif Fajar Solikin; Kusrini; Ferry Wahyu Wibowo (LPPM STMIK El Rahma Yogyakarta, 2022)
Intercomparison of mass quantities is an activity to compare performance between laboratories ofmass quantities and reference laboratories which produces intercomparative data in the form ofconventional mass values and uncertainty values. Clustering of weights was carried out to obtain ananalysis of the laboratory’s participants management. The analysis carried out is very dependent on theaccuracy of the cluster. Clustering using self-organizing maps algorithm, and the results are tested for thelevel of homogeneity within the cluster and the level of heterogeneity between clusters using the icdrate value.The clustering of intercomparison’s data using the self-organizing maps method resulted in an icdratevalue of 0,0713 for an artifact of 1000 g and an icdrate of 0,2889 for an artifact of 200g